Yahoo Web Search

  1. ( r ^(2)-36)/(( r +6)^(2)) The binomial can be factored using the difference...difference of squares formula is a^(2)-b^(2)=(a-b)(a+b). (( r -6)( r +6))/(( r +6)^(2)) Reduce the expression by canceling out...

    5 Answers · Science & Mathematics · 06/03/2010

  2. ((200)/( r +10))=((200)/( r ))-1 Remove the parentheses around the expression (200)/(( r +10)). (200)/( r +10)=((200)/( r ))-1 Remove... on the left-hand side of the equation. (- r +200)/( r )=(200)/( r +10) Since there...

    2 Answers · Science & Mathematics · 29/04/2010

  3. Assume that R has a divisor of 0, say a different than 0, thus there exists c in R ...contradiction. If aba = a, then abab = ab thus abab -ab = 0, thus a( bab - b)=0, as R has no divisors of 0 we have that bab = b. Take any a...

    3 Answers · Science & Mathematics · 11/05/2012

  4. R (x) = -2x³ - 7x + 14 R (11) = -2(11)³ - 7(11) + 14 R (11) = -2(1331) - 77 + 14 R (11) = -2662 - 77 + 14 R (11) = -2725

    3 Answers · Science & Mathematics · 03/07/2008

  5. Simplify: (square the top and bottom of the fraction, then multiply top by R : 22.4 = 14400R/( R +139)^2 Clear fraction: (multiply both ...

    2 Answers · Science & Mathematics · 21/10/2009

  6. Multiply by r : 1 - 1/2 r ^2 = 3/5 r 1/2 r ^2 + 3/5 r - 1 = 0 5 r ^2 + 6r - 10 = 0 And solve using the quadratic equation.

    3 Answers · Science & Mathematics · 05/08/2009

  7. r ^2h)/(2πrh+2π r ^2)<1/3 (π r ^2)/(2π r +2π r ^2)<1/3 (π r ^2)/2π r (1+ r )<1/3 r /2(1+ r )<1/3 r <...

    2 Answers · Science & Mathematics · 24/08/2012

  8. Note that: r ^2/( r + 4) => [( r ^2 - 16) + 16]/( r + 4) = ( r ^2 - 16)/( r + 4) + 16/( r + 4) = [( r + 4)( r - 4)]/( r + 4) + 16/( r + 4), by difference of two squares = ( r - 4) + 16/( r + 4). Thus, the integral becomes: ∫ r ^2/( r + 4) dr...

    6 Answers · Science & Mathematics · 28/06/2010

  9. let r = the radius of the base of the cone , we also have: R = radius of sphere R + x = height cone V... - 3x^2 = 0 ( R + x)( R - 3x) = 0 x = - R , R /3 => reject the negative root: x = R ...

    3 Answers · Science & Mathematics · 26/06/2015

  10. ∑ _{ r =1, n} 1= n ∑ _{ r =1, n} r = (n+1)·n/2 ∑ _{ r =1, n} r²= n·(n+1)·(2n+1)/6 ==>...2nr +r² -n - r ) = (n²-n)·∑ _{ r =1, n} 1 + (2n-1)· ∑ _{ r =1, n} r + ∑ _{ r =1, n} r² = (n²-n)·n + (2n-1)·(n...

    1 Answers · Science & Mathematics · 26/07/2009

  1. Try asking your question on Yahoo Answers